Distribution of Infiltration Wells for Surface Runoff Control in Bandung District - Riki Ridwana; Dede Sugandi; Arif Ismail; Jupri Jupri; Ar'rafi Malika Ardy (Universitas Pendidikan Indonesia, 2022)
The purpose of this study was to analyze the volume of surface runoff in the watersheds, the smallest land unit, and the distribution of infiltration wells to accommodate the volume of rainfall in Bandung Regency. The experimental research method is related to the volume of rainfall that must be controlled in each watershed. Landcover area is known by utilizing Landsat 8 OLI imagery in 2020. The calculation of rainfall intensity is needed to get the volume of rain. Samples were analyzed based on built-up land in each watershed. The built area of the Ci Widey watershed is 23.36 km2 and the volume of rainfall and runoff is 680,243 m3, built area of the Ci Sangkuy watershed is 20.05 km2, and the volume is 583,860 m3, built area of the Ci Rasea watershed is 11.74 km2 and the volume is 1258,275 m3, and built area of the Ci Tarik watershed is 68.59 km2 and the volume is 1997,340 m3. On a land unit of 100 m2, the volume of rainfall is 2,912 m3 and the lowest is 0.284 m3. Based on the land area of 100 m2, the distribution of the number of infiltration wells is Ci Widey 340, Ci Sangkuy 292, Ci Rasea 629, and Ci Tarik 999. Control of surface flow according to the volume of rainfall is inserted into infiltration wells that can accommodate a surface runoff volume of 2 m3. With the availability of infiltration wells, the surface flow can be controlled.